2013
DOI: 10.1016/j.psyneuen.2013.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Blunted cortisol response to stress is associated with higher body mass index in low-income preschool-aged children

Abstract: No known studies have tested the hypothesis that a blunted pattern of cortisol reactivity to stress, which is often found following exposure to chronic life stressors, is associated with a higher body mass index (BMI) in very young children. Low-income children (n = 218, mean age 56.6 (range: 38.1 to 78.5; SD 7.0) months, 49.1% male, 56.4% white, 16.1% black, 11.5% Hispanic/Latino) participated in a series of behavioral tasks designed to elicit stress. Cortisol was sampled in saliva 5 times during the protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…61 in this study, cortisol levels did not vary significantly with age or sex. A small number of other studies [62][63][64] examining either basal cortisol levels or cortisol responses to stress confirm these results; however, other studies do not. 65,66 in our sample, although OC had a significantly lower AUC compared to controls, this difference was lost after inserting the effect of age.…”
Section: Discussionmentioning
confidence: 87%
“…61 in this study, cortisol levels did not vary significantly with age or sex. A small number of other studies [62][63][64] examining either basal cortisol levels or cortisol responses to stress confirm these results; however, other studies do not. 65,66 in our sample, although OC had a significantly lower AUC compared to controls, this difference was lost after inserting the effect of age.…”
Section: Discussionmentioning
confidence: 87%
“…A study on a selected low-income group of preschool children found similar associations of increased BMI (BMI z-scores) and blunted HPA stress reactivity [17]. This limited capacity to respond to challenging conditions might be the result of limited coping strategies, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This limited capacity to respond to challenging conditions might be the result of limited coping strategies, i.e. maladaptive or unhealthy strategies such as potential changes in food consumption to manage stress conditions [17, 58]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations